Analisa Usulan Perbaikan Tata Letak Fasilitas untuk Mengoptimalkan Proses Produksi pada CV. XYZ dengan Metode Systematic Layout Planning - Ridwan, Muhamad; Intani, Arvita Emarilis; Listyanto, Rudy Effendi (Universitas Harapan Medan, 2025)
An efficient facility layout is crucial for improving productivity and operational efficiency, especially for Small and Medium Enterprises like CV. XYZ, which face space limitations and inefficient material flow. This study aims to redesign the facility layout using the Systematic Layout Planning (SLP) method to optimize material flow, reduce internal transportation, and enhance the competitiveness of CV. XYZ in the screen printing industry. A quantitative descriptive approach was employed, with data collected through observations, interviews, documentation, and literature review. The SLP stages include activity analysis, calculation of Material Handling Costs (MHC), creating a from-to chart, priority scale table, activity relationship chart, and layout simulation using Blocplan software. The results show that the proposed layout successfully reduced the distance between workstations, optimized the process flow, and decreased MHC by 7% or IDR 15,648.75. These changes enhanced production efficiency, minimized material handling time, and created a more organized and productive layout. By effectively redesigning the facility layout, CV. XYZ improved its operational efficiency.